Association between neonatal resuscitation and a single nucleotide polymorphism rs1835740. (13th May 2016) - Odd, David; Váradi, Anikó; Rajatileka, Shavanthi; Molnár, Elek; Luyt, Karen
Abstract: Aim: The aim of this work was to test whether three single nucleotide polymorphisms (SNPs) implicated in glutamate homoeostasis or signalling and cellular survival are associated with birth condition. Methods: This study is drawn from the Avon Longitudinal Study of Parents and Children. A total of 7611 term infants were genotyped and patient outcome data retrieved from routine medical records. Exposure measures were the presence of one or more minor alleles in one of 3 SNPs (rs2284411, rs2498804, rs1835740). The primary outcome was the need for resuscitation at birth. Results: For SNP rs1835740, infants homozygous for the minor allele compared to wild type were more likely to need resuscitation (9.2% vs. 7.0%, p = 0.041), while the odds ratio for resuscitation was associated with each increasing minor allele [OR 1.17 (1.01–1.35)]. Population attributable risk fraction was 6.5%. There was no evidence that the other two SNPs investigated were associated with birth condition. Conclusion: We have tested three candidate SNPs to measure any association with birth condition. The study revealed that the rs1835740 was associated with the need for resuscitation and Apgar scores, with a substantial population impact.